Needlescopic video-assisted thoracic surgery for reversal of thoracic sympathectomy - Wong, Randolph H.L. (Oxford University Press, 2012)
Thoracic sympathectomy is a commonly performed surgical procedure for the treatment of palmar hyperhidrosis. However, one major complication of such a procedure is compensatory truncal hyperhidrosis. We describe an extreme case of compensatory truncal hyperhidrosis and anhidrosis over the head and neck region which led to a heatstroke. Bilateral reoperative needlescopic video-assisted thoracic surgery was performed for the reversal of thoracic sympathectomy with an interposition intercostal nerve graft. The patient's truncal hyperhidrosis resolved gradually over 1 month following the reversal procedure.